Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.3354/meps340207
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of meiobenthos in the Nazaré canyon and adjacent slope (western Iberian Margin) in relation to sedimentary composition

Abstract: Abundance of metazoan meiofauna and foraminifera, and biomass and community structure of nematodes, were investigated in the benthic zone along the Nazaré Canyon and adjacent continental slope in relation to concentration of organic matter and its suitability as a food source for the meiobenthos. The Nazaré canyon sediments were richer in organic carbon (Corg), total nitrogen, and phytopigments than the adjacent open slope. In addition, phytodetritus was fresher in the canyon sediment than on the slope (higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 32 publications
(29 reference statements)
2
60
3
Order By: Relevance
“…In contrast, Garcia et al (2007) found that non-selective deposit feeders were more important in canyons than on the continental slope. The localities studied by Garcia et al (2007) were much more disturbed (near canyon axis) compared to the sediment draped terrace studied here and so we suggest that intense recurrent hydrodynamic activity at their sites is (partially) responsible for this discrepancy.…”
Section: Environmental Conditions In the Nazaré Canyon And Their Inflmentioning
confidence: 40%
See 4 more Smart Citations
“…In contrast, Garcia et al (2007) found that non-selective deposit feeders were more important in canyons than on the continental slope. The localities studied by Garcia et al (2007) were much more disturbed (near canyon axis) compared to the sediment draped terrace studied here and so we suggest that intense recurrent hydrodynamic activity at their sites is (partially) responsible for this discrepancy.…”
Section: Environmental Conditions In the Nazaré Canyon And Their Inflmentioning
confidence: 40%
“…In contrast, Garcia et al (2007) found that non-selective deposit feeders were more important in canyons than on the continental slope. The localities studied by Garcia et al (2007) were much more disturbed (near canyon axis) compared to the sediment draped terrace studied here and so we suggest that intense recurrent hydrodynamic activity at their sites is (partially) responsible for this discrepancy. In addition, non-selective deposit feeders have been known to exhibit recolonisation ability after severe disturbance, but in less disturbed environments they are less dominant (Lee et al, 2001a).…”
Section: Environmental Conditions In the Nazaré Canyon And Their Inflmentioning
confidence: 40%
See 3 more Smart Citations